Splinters in your eye: Frankfurt school provocations - Jay martin (London Verso, 2020)
Although successive generations of the Frankfurt School have attempted to adapt Critical Theory to new circumstances, the work done by its founding members continues in the 21st century to unsettle conventional wisdom about culture, society and politics.